2016
DOI: 10.31949/jcp.v2i2.335
|View full text |Cite
|
Sign up to set email alerts
|

Peningkatan Keterampilan Proses Sains Siswa Sekolah Dasar Melalui Model Pembelajaran Berbasis Masalah

Abstract: Penelitian ini didasarkan pada masih rendahnya kualitas pembelajaran di SD dalam mengimplementasikan pembelajaran yang dapat meningkatkan keterampilan proses sains. Berdasarkan alasan tersebut tujuan penelitian ini yaitu untuk mendeskripsikan apakah data peningkatan keterampilan proses sains siswa yang mendapatkan pembelajaran berbasis masalah (PBM) lebih baik dibandingkan siswa yang mendapatkan pembelajaran bukan PBM. Metode penelitian yang digunakan yaitu quasi eksperiment dengan desain pre-and post test des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
15

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 0 publications
0
12
0
15
Order By: Relevance
“…In the field of MIPA, the quality of education in Indonesia is also low [1]. The results of the TIMSS (Trends in International Mathematics and Science Study) survey measuring the scientific inquiry ability showed that the average score of Indonesian students' science achievement in 1999 was 435, making Indonesia the 32nd place out of 39 countries, in 2003 on the order 37 out of 46 countries with an average score of 420, as well as the results in 2007 are in the order of 35 out of 49 countries with an average score of 427, and the results of the 2011 survey also show relatively similar results, which are in the order of 39 of 41 countries with the average score of 406 while the average international score has reached the score of 500 [2] [3].…”
Section: Introductionmentioning
confidence: 56%
“…In the field of MIPA, the quality of education in Indonesia is also low [1]. The results of the TIMSS (Trends in International Mathematics and Science Study) survey measuring the scientific inquiry ability showed that the average score of Indonesian students' science achievement in 1999 was 435, making Indonesia the 32nd place out of 39 countries, in 2003 on the order 37 out of 46 countries with an average score of 420, as well as the results in 2007 are in the order of 35 out of 49 countries with an average score of 427, and the results of the 2011 survey also show relatively similar results, which are in the order of 39 of 41 countries with the average score of 406 while the average international score has reached the score of 500 [2] [3].…”
Section: Introductionmentioning
confidence: 56%
“…Science process skills are all skills needed to acquire, develop, and apply the concepts, principles, laws, and theories of science in the form of mental ability, physics, and social skills [20]. Physics Education Students come from backgrounds in different schools.…”
Section: Resultsmentioning
confidence: 99%
“…Science process skills are the abilities needed to acquire, develop, and apply concepts, principles, laws, and scientific theories in the form of mental, physical, and social skills [15]. Science process skills help students learn through knowledge to solve problems and find solutions [16].…”
Section: Introductionmentioning
confidence: 99%